Parent Reports of Developmental Service Utilization After Newborn Screening - Elizabeth Reynolds; Sarah Nelson Potter; Samantha Scott; Donald B. Bailey (International Journal of Neonatal Screening)
Newborn screening (NBS) presents an opportunity to identify a subset of babies at birth who are at risk for developmental delays and could benefit from a range of developmental services. Potential developmental services in the United States include Part C Early Intervention (EI), private therapies, and school-based services. Using parent-reported outcomes, this study examined the rates at which a sample of children diagnosed with NBS conditions used each developmental service. An online survey of 153 parents representing children with 27 different NBS conditions found that nearly 75% of children (n = 112) used at least one developmental service, with private therapies being the most frequent. Children were referred to EI relatively early and were often eligible because their medical diagnosis automatically qualified them. When examining condition-specific results for children with severe combined immunodeficiencies, congenital hypothyroidism, and Pompe disease, we found variability in rates of use, with high rates overall. Our findings suggest that many children diagnosed with an NBS condition continue to have developmental delays even after they receive appropriate medical care. Future research with more systematic follow-up is needed to understand whether the NBS program facilitates entry into these services and whether more streamlined processes could benefit children and families.